Affective and cognitive behavior is not altered by chronic constriction injury in B7-H1 deficient and wildtype mice - Franziska Karl; Maria B. Nandini Colaço; Annemarie Schulte; Claudia Sommer; Nurcan Üçeyler (BMC Neuroscience, 2019)
Abstract Background Chronic neuropathic pain is often associated with anxiety, depressive symptoms, and cognitive impairment with relevant impact on patients` health related quality of life. To investigate the influence of a pro-inflammatory phenotype on affective and cognitive behavior under neuropathic pain conditions, we assessed mice deficient of the B7 homolog 1 (B7-H1), a major inhibitor of inflammatory response. Results Adult B7-H1 ko mice and wildtype littermates (WT) received a chronic constriction injury (CCI) of the sciatic nerve, and we assessed mechanical and thermal sensitivity at selected time points. Both genotypes developed mechanical (p < 0.001) and heat hypersensitivity (p < 0.01) 7, 14, and 20 days after surgery. We performed three tests for anxiety-like behavior: the light–dark box, the elevated plus maze, and the open field. As supported by the results of these tests for anxiety-like behavior, no relevant differences were found between genotypes after CCI. Depression-like behavior was assessed using the forced swim test. Also, CCI had no effect on depression like behavior. For cognitive behavior, we applied the Morris water maze for spatial learning and memory and the novel object recognition test for object recognition, long-, and short-term memory. Learning and memory did not differ in B7-H1 ko and WT mice after CCI. Conclusions Our study reveals that the impact of B7-H1 on affective-, depression-like- and learning-behavior, and memory performance might play a subordinate role in mice after nerve lesion.